EFEKTIVITAS PEMBELAJARAN FIQIH BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Irfan, Muchammad; Badruzzaman, Moh. Hilal; Mahbubi, M (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2025)
The purpose of this study is to examine the effectiveness of problem-based learning (PBL) in Fiqh instruction in improving students’ critical thinking skills at Madrasah Aliyah. The main problem underlying this research is the low ability of students to think critically and apply Islamic legal principles in real-life situations. This study employed a descriptive qualitative approach through a case study design. The research subjects consisted of thirty eleventh-grade students from a state Madrasah Aliyah in Banyuwangi that implemented the problem-based learning model. Data were collected through classroom observations, in-depth interviews, and document analysis, and then analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the PBL model significantly enhances students’ critical thinking skills. Students demonstrated improvement in analyzing legal issues, evaluating shar‘i arguments, and formulating relevant legal conclusions for contemporary life problems. Through discussion, teamwork, and reflection on Islamic values in class, PBL not only fostered cognitive development but also nurtured scientific and religious character. Therefore, problem-based Fiqh learning is considered effective in simultaneously enhancing critical thinking and deepening religious understanding. These findings align with the principles of the Kurikulum Merdeka, which emphasize active learning, critical reasoning, and the development of students’ cognitive abilities.